Social Connectivity During the COVID-19 Pandemic: Disparities among Medicare Beneficiaries. (July 2021) - Jacobs, Molly; Ellis, Charles
Purpose: Social connections are essential for health and well-being at all ages and may be especially important for promoting health in later life. Maintaining social connections, however, became increasingly difficult during the COVID-19 pandemic when stay-at-home orders were enacted, and social distancing became necessary. This study examines the social connectivity among Medicare beneficiaries during the COVID-19 pandemic highlighting the importance technological availability, income, and race. Methods: Data from the 2020 Medicare Beneficiaries Survey COVID supplement was used to evaluate social connectedness during the spring and fall of 2020. Binomial logistic regression evaluated the relationship between feelings of social connectedness and race/ethnicity, urban status of residence, income, availability of household technologies, internet access, and chronic conditions. Results: Lower social connectivity is significantly correlated with race and income. Blacks had a nearly 30% higher likelihood of feeling socially disconnected than other racial groups. Individuals with chronic conditions, particularly cancer, were significantly more likely to feel socially disconnected. Internet access and the availability of technological devices decreased the odds of feeling socially disconnected by 20% and 15% respectively. Conclusion: The COVID-19 pandemic decreased the social connectedness of many vulnerable groups specifically Blacks, those living with chronic conditions, and individuals with limited access to technology. While it is outside the scope of the current study, additional research is needed to determine how to address the social and psychological impacts of the COVID-19 pandemic among elderly Americans.